2016
DOI: 10.1007/s00401-015-1530-0
|View full text |Cite
|
Sign up to set email alerts
|

Pur-alpha regulates cytoplasmic stress granule dynamics and ameliorates FUS toxicity

Abstract: Amyotrophic lateral Sclerosis is characterized by progressive loss of motor neurons in the brain and spinal cord. Mutations in several genes, including FUS, TDP43, Matrin 3, hnRNPA2 and other RNA binding proteins, have been linked to ALS pathology. Recently, Pur-alpha a DNA/RNA binding protein was found to bind to C9orf72 repeat expansions and could possibly play a role in the pathogenesis of ALS. When overexpressed, Pur-alpha mitigates toxicities associated with Fragile X tumor ataxia syndrome (FXTAS) and C9o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 75 publications
11
74
0
Order By: Relevance
“…Recent reports suggest these granules are membraneless organelles, partially or wholly stabilized by liquid–liquid phase separation (LLPS) where molecules self segregate (demix) to form two co‐existing liquids as observed for oil droplets in water (Courchaine et al , 2016). However, unlike oil–water emulsions, RNP granules formed by LLPS are not devoid of water and are thought to be stabilized by multivalent, dynamic protein:protein and protein:mRNA interactions, concentrating granule components into a dense and viscous compartment into which other molecules can partition and localizing their cellular function (Ryu et al , 2014; Burke et al , 2015; Di Salvio et al , 2015; Lenzi et al , 2015; Bowden & Dormann, 2016; Daigle et al , 2016; Nott et al , 2016). Indeed, FUS‐containing granules and FUS at sites of DNA damage have liquid‐like properties in cells (Patel et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest these granules are membraneless organelles, partially or wholly stabilized by liquid–liquid phase separation (LLPS) where molecules self segregate (demix) to form two co‐existing liquids as observed for oil droplets in water (Courchaine et al , 2016). However, unlike oil–water emulsions, RNP granules formed by LLPS are not devoid of water and are thought to be stabilized by multivalent, dynamic protein:protein and protein:mRNA interactions, concentrating granule components into a dense and viscous compartment into which other molecules can partition and localizing their cellular function (Ryu et al , 2014; Burke et al , 2015; Di Salvio et al , 2015; Lenzi et al , 2015; Bowden & Dormann, 2016; Daigle et al , 2016; Nott et al , 2016). Indeed, FUS‐containing granules and FUS at sites of DNA damage have liquid‐like properties in cells (Patel et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also identified de novo mutations in the PURA gene, which encodes Pur-alpha, that are associated with neonatal hypotonia, encephalopathy with or without seizures, neurodevelopmental delays, learning disabilities, and poor coordination or ataxias in several young human subjects (Hunt et al, 2014, Lalani et al, 2014, Tanaka et al, 2015). Dysregulation of Pur-alpha has also been shown in C9Orf72-related Frontotemporal lobe dementia in association with Amyotrophic Lateral Sclerosis, presumably resulting from accumulation of intracellular inclusion bodies that contain Pur-alpha and RNA complexes, and RNA toxic gain-in-function effects (Daigle et al, 2016). Pur-alpha may even be involved in enhancing HIV-1 transcription, with increasing concentrations of Pur-alpha leading to increased transcription of HIV-1 (Chepenik et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…) could further impair SG assembly in C9orf72 mutation carriers, as Pur‐α appears to be essential for SG formation (Daigle et al . ). Although these results have to be reconciled with the conflicting finding that TDP‐43 inclusions in C9orf72 patients frequently are SG marker (PABP1) positive (McGurk et al .…”
Section: Many Als/ftld‐associated Genes Affect Sg Dynamicsmentioning
confidence: 97%